2020
DOI: 10.1002/ejp.1612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurofeedback in the management of chronic pain: A systematic review and meta‐analysis of clinical trials

Abstract: Background and ObjectiveNeurofeedback (NFB) provides real‐time feedback about neurophysiological signals to patients, thereby encouraging modulation of pain‐associated brain activity. This review aims to evaluate the effectiveness and safety of NFB in alleviating pain and pain‐associated symptoms in chronic pain patients.MethodsMEDLINE, PUBMED, Web of Science and PsycINFO databases were searched using the strategy: (“Neurofeedback” OR “EEG Biofeedback” OR “fMRI Biofeedback”) AND (“Pain” or “Chronic Pain”). Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 44 publications
9
56
0
1
Order By: Relevance
“…In general, neurofeedback sessions tend to be 30-45 minutes long and patients are offered 20-40 sessions [15]. The frequency of these sessions ranges from one to five times a week, but studies which administered more frequent sessions have reported greater pain relief.…”
Section: Neurofeedback Training Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, neurofeedback sessions tend to be 30-45 minutes long and patients are offered 20-40 sessions [15]. The frequency of these sessions ranges from one to five times a week, but studies which administered more frequent sessions have reported greater pain relief.…”
Section: Neurofeedback Training Protocolsmentioning
confidence: 99%
“…The frequency of these sessions ranges from one to five times a week, but studies which administered more frequent sessions have reported greater pain relief. Commonly used electrodes for providing feedback include C3, C4, Cz, T3, T4, FP1, P3 and P4 [15]. DOI: http://dx.doi.org /10.5772/intechopen.93826 Feedback has been provided in a range of ways.…”
Section: Neurofeedback Training Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these systematic reviews were inconclusive due to the limited data. While a recent review found a medium effect size of pain reduction favoring neurofeedback interventions in chronic pain, it included studies using functional magnetic resonance imaging-based neurofeedback [ 24 ]. Combining the results for 2 different methodologies makes it difficult to evaluate the analgesic effect of a specific intervention.…”
Section: Introductionmentioning
confidence: 99%